Lahir dan Berkembangnya Trend Instagram Brow di Industri Kecantikan - Maria Margaretha Earlene (Bina Nusantara University, 2020)
An eyebrow makeup trend called Instagram Brow (InstaBrow) with 253,388 #instabrows uploads and 35,572 #instabrow uploads on Instagram. This study analyzes the background and definition of instabrow. The Netnography method used for this qualitative research because of its relation to the internet and ethnography (Kozinets, 2010). The data collection is done through the Sprinklr application, as well as observations on Instagram uploads, and the involvement of researchers as beauty influencers on Instagram. Discourse Analysis is used to compare the data with interview articles on popular news media websites about annual eyebrow trends. Instabrow is influenced by the method of eyebrow formation with the Golden Ratio principle from Anastasia Soare. Anastasia Beverly Hills (ABH), her makeup brand, though it doesn’t promote #instabrows, ABH is often mentioned along with the hashtag. Beauty businesses that promote the term “Instabrow” are Microblading services, provide semi-permanent eyebrows the consumer desire. The goal is for consumers who want beautiful eyebrows without having the need to waste time or energy every day. Celebrities such as Kylie Jenner with her distinctive eyebrow makeup helped with the popularity of Instabrow. Jenner now benefits from the trend by launching a variety of her eyebrow makeup products. Many professional makeup artists predicted the end of the instabrow trend since 2014, while even now the trend has not yet ended. Variations began to emerge, but the instabrow trend remains, even reached its peak in September 2018. The main reason makeup enthusiasts love it is how it is attractive in photos. The results of this study are expected to provide an overview of the beauty industry regarding the phenomenon of instabrow trends on Instagram.